2017
DOI: 10.1007/s11356-017-8805-z
|View full text |Cite
|
Sign up to set email alerts
|

The potential DNA toxic changes among workers exposed to antimony trioxide

Abstract: Occupational exposure to antimony has gained much interest when specific toxic effects were noticed among workers processing antimony. Thus, the aim of the present work was to investigate the potential DNA oxidative damage occurring among Egyptian workers occupationally exposed to antimony trioxide. The study was conducted on 25 subjects exposed to antimony trioxide while working in the polymerization process of polyester in Misrayon and Polyester Fiber Company, KafrEldawwar, Beheira, Egypt. Urinary antimony l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Repeated exposure to alpha-CYP pesticides appears to lead to p53 gene mutations (El Okda et al, 2017). A genotoxic impact for occupationally exposed antimony trioxide individuals was also reported with DNA damage detected in the form of increased apurinic/apyrimidic sites (El Shanawany et al, 2017). Interindividual variation in adduct levels associated with benzene and PAHs may reflect genetic susceptibility as well (Ayi-Fanou et al, 2011).…”
Section: G X E and Related Integration Of Genomic And Environmental Ementioning
confidence: 99%
See 1 more Smart Citation
“…Repeated exposure to alpha-CYP pesticides appears to lead to p53 gene mutations (El Okda et al, 2017). A genotoxic impact for occupationally exposed antimony trioxide individuals was also reported with DNA damage detected in the form of increased apurinic/apyrimidic sites (El Shanawany et al, 2017). Interindividual variation in adduct levels associated with benzene and PAHs may reflect genetic susceptibility as well (Ayi-Fanou et al, 2011).…”
Section: G X E and Related Integration Of Genomic And Environmental Ementioning
confidence: 99%
“…A variety of biomarkers were incorporated into various studies, especially to monitor kidney injury or dysfunction (Samir and Aref, 2011;Cabral et al, 2012;Cabral et al, 2015). Some heavy metals' association with lipid peroxidation, DNA damage, oxidative stress, or apoptosis was assessed (El-Baz et al, 2015;Bortey-Sam et al, 2018) and the genotoxic impact of some occupational exposures was explored (El Shanawany et al, 2017).…”
Section: Exposures Measuredmentioning
confidence: 99%
“…Antimony is one of the heavy metals with high bio‐toxicity at low concentration . It can influence human beings' health deeply and cause serious diseases such as lung irritation, albuminuria, glycosuria, non‐malignant respiratory heart diseases and so on . Recently, the pollution of antimony in the dyeing and printing wastewater is particularly concerned by the Chinese government and the upper limit of antimony in textile dyeing and finishing industry water pollutant is stipulated to be 0.1 mg · L –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Taiwan has also adopted the 8 h time weighted average concentration of antimony and its compounds in the air of workplace at a level of 0.5 mg/m 3 [ 8 ]. Antimony and its compounds may irritate eyes, skin, and respiratory systems, and are suspected to be carcinogenic and teratogenic substances [ 1 , 9 , 10 , 11 , 12 , 13 ]. In an animal study, among rats exposed to substances containing Sb, only female rats developed lung cancer; 27% in those rats exposed to antimony trioxide and 25% in those rats exposed to antimony ore had the cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grosskopf et al reported that trivalent antimony was responsible for genotoxicity in the cellular system because antimony could partly impair the pathway of nucleotide repair [ 11 ]. DNA damage has been detected for workers with occupational exposure to antimony trioxide [ 12 , 13 ]. International Agency for Research on Cancer (IARC) has classified trivalent antimony as a possible human carcinogen [ 14 ].…”
Section: Introductionmentioning
confidence: 99%